Ácaros asociados al coleóptero Passalus cognatus (Coleoptera: Passalidae) de Los Tuxtlas, Veracruz, México - A. Villegas Guzmán, Gabriel; M. Pérez, Tila; Reyes Castillo, Pedro (Revista de Biología Tropical, 2008)
There are few records of mites associated with the tropical coleopterans of Mexico. We examined 35 passalid beetles (bessbugs) Passaluscognatus from Los Tuxtlas region in Veracruz State, Mexico. Twenty of them had a total of 245 mites (representing eight species, eight genera, eight families and three suborders). The most abundant species were Uroobovellacaliforniana Wisniewski & Hirschmann (35%), Euzerconhyatti Hunter & Rosario (20%), and Uropoda sp. (17.5%). The preferred attachment areas were the coxae; followed by the mesosternum and the humeri. Each beetle had 1 to 40 mites (average: 12); and we found 1-4 mite species per beetle.